Electoral System and Level of Party Fragmentation in Republic of Bulgaria (1991 – 2001) - Tsenova, Radka (Research Papers, 2005)
Electoral system has a direct effect over the intensity of the competitive and cooperative relations between the political parties on an electoral and parliamentary level, which determines in a great extent the form of the party system and the parties fragmentation. The present study is dedicated to the analysis of the active electoral system in the Republic of Bulgaria during the period 1991-2001, as well as to its influence over the parties fragmentation within the country.In the First Part of the study it is given a short description of the proportional system in the multimandate electoral regions (MERs), as well as its effects. There are formed the main thesis of the Study hypotheses.In the Second Part are reviewed the main approaches of research of the degree of the influence of the electoral systems over the parliamentary systems and the degree of parties fragmentation. In the Third Part, the Bulgarian electoral system is characterized and some assumptions are formed in regard to its effects.In the Forth Part, it is presented a detailed analysis of the Bulgarian case and are formed the results of the Study, which support the thesis that the proportional electoral system in the MERs, due to the methods for distribution of the mandates and the V. P. Ondt’s method (rule) in particular, as well as the high 4 % electoral barrier, provides different bales of disproportional effect on the parliamentary elections in Bulgaria within the period 1991-2001. This effect has its highest value in 1991 and the lowest one in 1997. This objectively determines the limited (low) fragmentation of the parliamentary party system as the number of the relevant and/or effective parties from one election to another is limited – from 3 to 5 parties or coalitions under the „numeral criterion“. There is a concentration effect of the electoral system over the party system.The effectiveness of the proportional system in the MERs in Bulgaria within the period 1991 – 2001 depends not so much on the concentration of the party system, but on the political behavior of the parliamentary majorities and the opposition. And this is the major reason for the political government and even institutional instability in 1991-1997. The financial and internal political stability which occurred in Bulgaria in 1997-2001, as well as the opening of Bulgaria towards the European structures, happened in return to the negative consequences of the concentration of power resources and partocracy, instead of the control and balance of the three powers, corruption and clientelism of the different political structures, the party conflicts and partisanship and the decrease in the interaction of the parliamentary parties with other party formations and most over with structures of the Civil Society.Two trends occurred – of marginalization of the small parties and of some relevant party formations such as BBB and the Eurolefts, and of a deepening electoral absentism (unwillingness to vote), which highest point was recorded in 1997.